Municipal recycling performance in Victoria, Australia: results from a survey of local government authorities. Issue 3 (2nd July 2020) - Agarwal, Priya; Werner, Tim T.; Lane, Ruth; Lamborn, Julia
ABSTRACT: In Australia, local government authorities play an essential role in diverting waste from landfill, including through domestic waste recycling. To date, the effectiveness of these recycling operations in Australia has not been thoroughly investigated. This study assessed recycling performance in the state of Victoria through a survey of all 79 municipal councils. This survey identified key challenges affecting successful domestic waste management, primarily relating to contamination in recycling streams, stemming from residents' inability to differentiate between recyclable and non-recyclable materials. Councils were concerned about inconsistent waste management practices between councils, and highlighted that revising Australian Standard AS4123.3 to standardise bin lid colours could reduce community confusion. Many councils faced information gaps, which could be resolved by including more performance indicators in the Local Government Performance Reporting Framework. Drivers of recycling performance were also considered through multiple regression, using data from the survey, the Australian Bureau of Statistics, and other government sources. This analysis supported the councils' identification of high service costs and residents' inability to differentiate between recyclable and non-recyclable materials as key issues. An extension of this quantitative approach to other Australian jurisdictions exposed significant data gaps, indicating the need for a more consistent national data collection policy.